Posthuman Aesthetics and Cultural Hybridity in Chinese Ballet Development - Li, Zhe; Natayakulwong, Sirimongkol (Journal of Posthumanism, 2025)
This study investigates posthuman aesthetics and cultural hybridity in the development of Chinese ballet. This genre has evolved from Soviet-influenced classical foundations into a unique, intercultural, and technologically infused performance form. Drawing on performance analysis, field observations, document review, and interviews with five key informants—including choreographers and directors—this qualitative research explores how Chinese hybrid ballet transcends anthropocentric and nationalistic boundaries. Case studies of productions such as Century, Dream of the Red Chamber, and The Red Detachment of Women reveal how the dancer’s body becomes a posthuman interface, intertwined with digital scenography, mythological narrative, and cultural symbolism. These ballets do not merely merge East and West but operate within a “third space,” reconfiguring narrative, movement, and visual design to challenge aesthetic conventions. Fieldwork at the Central Ballet Company and visual ethnography illustrate the active roles of multimedia, folk gestures, and symbolic costuming in shaping embodied hybridity. Audience feedback underscores the performances' emotional and cultural resonance, particularly among younger viewers who see hybrid ballet as heritage and innovation. The research contributes to broader posthumanist` discourse by highlighting how non-Western dance forms engage with technology, pedagogy, and identity. Future research should explore cross-cultural comparisons, dancer training models, and digital audience interaction further to contextualize the implications of this evolving aesthetic paradigm.